PENGARUH MODEL KOOPERATIF TIPE CONCEPT SENTENCE TERHADAP KETERAMPILAN MENULIS TEKS NARASI SISWA - Elda Listi Regina; Anni Malihatul Hawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of the Concept Sentence cooperative model assisted by Bianglala Pop Up Edukasi (BPUPKI) media on students' narrative text writing skills. The problem faced is the low narrative text writing skills of students in the learning process. This study used a quantitative approach with the population being all students of SDN Ungaran 01, while the samples were students of classes IV A and IV B of SDN Ungaran 01. Data analysis was carried out through normality tests, homogeneity tests, independent sample t-test and regression tests. The results showed: (1) There was a significant difference between the experimental class using the Concept Sentence cooperative model assisted by Bianglala Pop Up Edukasi (BPUPKI) media and the control class using the Concept Sentence cooperative model without Bianglala Pop Up Edukasi (BPUPKI) media, with a significance value of 0.000 < 0.05 based on the independent sample t-test. (2) There was an effect of the Concept Sentence cooperative model assisted by Bianglala Pop Up Edukasi (BPUPKI) media on students' narrative text writing skills, with a significance value of 0.000 < 0.05 based on the regression test. The conclusion of this study is that the Concept Sentence cooperative model assisted by Bianglala Pop Up Edukasi (BPUPKI) media is effective in improving students' narrative text writing skills.